The Financial Ripple Effect: Evaluating the Impact of Corporate Downsizing in Meta - Aaron Kevin Sammy Tatengkeng; Sylviana Maya Damayanti; Jagat Prirayani (Publikasi Indonesia, 2025)
This study examines the financial ramifications of corporate downsizing on Meta Platforms Inc., focusing on the timeframe from 2018 to 2025, which includes the company's rapid growth and the ensuing